Lancashire Sketches : Third Edition - Waugh, Edwin, 1817-1890 (Salt Lake City, UT : Project Gutenberg, 2014)
"Lancashire Sketches" by Edwin Waugh is a collection of local sketches written in the late 19th century. The work draws on the author's intimate knowledge of South Lancashire, presenting rich descriptions of local scenery, points of interest, and elements of the region's history and culture. The sketches celebrate the everyday life of the Lancashire people and highlight the unique dialect of the area. The opening of the book introduces the charming village of Bardsea, located near Morecambe Bay. Waugh describes the tranquil summer atmosphere, the idyllic scenery, and a visit with a friend that includes playful children and a lively dog. The narrator and his friend embark on an adventure to Chapel Island, which involves wading through rising tides and encountering the island's only inhabitant, an old fisherman's wife. This gripping narrative combines elements of local history with a vivid portrayal of the Lancashire landscape and its people, setting the tone for the rest of the sketches to follow. (This is an automatically generated summary.)
Chapel Island; or, an adventure on the Ulverstone sands -- Ramble from Bury to Rochdale -- The cottage of Tim Bobbin, and the village of Milnrow -- The birthplace of Tim Bobbin -- Ramble from Rochdale to the top of Blackstone Edge -- The town of Heywood and its neighbourhood -- The grave of Grislehurst Boggart -- Boggart Ho' Clough -- Rostherne Mere -- Oliver Fernleaf's watch -- Norbreck: a sketch on the Lancashire coast -- Wandering minstrels; or, wails of the workless poor -- A wayside incident, during the cotton famine -- Saint Catherine's Chapel; or, the pretty island bay -- The knocker-up -- The complaint of a sad complaint.
Release date is 2014-06-24
E-text prepared by Les Galloway, sp1nd, and the Online Distributed Proofreading Team (http://www.pgdp.net) from page images generously made available by Internet Archive (https://archive.org)
Keywords: Lancashire (England) -- Social life and customs; Lancashire (England) -- Description and travel